Gastrovesical fistula as a rare complication following endoscopic transluminal drainage of walled-off necrosis-a case report - Špička, Petr; Vaněk, Petr; Chudáček, Josef; Falt, Přemysl; Hruška, František; Řezáč, Tomáš; Ambrož, Radek; Molnár, Ján; Zbořil, Pavel; Vrba, Radek; Klos, Dušan (AME case reports, 2024)
BACKGROUND: This study highlights an unusual and previously unreported adverse event (AE) following the minimally invasive treatment of pancreatic walled-off necrosis (WON). The standard treatment for WON currently involves primary drainage via an ultrasound-guided endoscopic, typically transgastric, approach. This method is associated with lower mortality and morbidity rates compared to traditional surgery. However, emerging AEs from these procedures may necessitate the involvement of a multidisciplinary team. Our case highlights the potential for gastrovesical fistula development as a rare AE following endoscopic drainage. Treatment for our patient prioritized individualized and non-surgical strategy, although surgical revision was also considered. CASE DESCRIPTION: A 42-year-old male presented with a large symptomatic pancreatic WON refractory to conservative management, necessitating transgastric drainage. Despite the gradual evacuation of the WON contents, treatment was complicated by stent-related issues, including inadvertent bladder penetration. Rather than surgical correction, a collaborative approach among urology, gastroenterology, and surgery teams was employed, focusing on conservative treatment strategies. This approach successfully resolved the fistula, leading to the patient's full recovery. CONCLUSIONS: Given the increasing use of endoscopic transluminal drainage in (peri)pancreatic collections, it is crucial to be aware of all potential AEs. To our knowledge, this is the first documented case of gastrovesical fistula following drainage of WON. Early recognition and a multidisciplinary approach are vital to manage this event.
Keywords: endoscopic drainage; walled-off necrosis (WON); gastrovesical fistula; case report; Necrotizing pancreatitis (NP)